PENGEMBANGAN PENDEKATAN DIKLAT BAHASA INGGRIS UNTUK PENINGKATAN KAPASITAS PESERTA DIKLAT - Irene - Nusanti (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2017)
The purposes of this article are to provide a description of developing an approach: 1) for self development-based English learning using daily routines as the topic, and 2) for self development-based English learning practice to develop the capacity of the training participants. So far, English training is more concentrated on the mastery of English and how to teach it. Therefore, it is proposed to develop an approach focusing on learning English to optimize the development of oneself by implementing tasks given. The study of self development-based English learning was done through a comprehensive analysis on literature study towards a number of references relating to concept of training, selfdevelopment concept, daily habits, and theory of learning. The study towards concept of training reminds us that design and content of training must be adopted to the shifting era which trains the participants to develop thinking skills in order to solve the problems in their lives. Self-development concepts show that the practice of good values on daily basis will make the training participants develop their capacity. The study towards daily habits expose that people become what they do daily consciously or unconsciously. While the study towards learning theory shows that learning will be more beneficial if the training participants know the benefit of what they learn. Thus, it can be concluded, the study of self development-based English learning with the emphasis on putting powerful daily routines into practice can be used to develop the capacity of the training participants through powerful daily routines. Abstrak: Penulisan artikel ini bertujuan untuk: 1) memberikan gambaran tentang pengembangan pendekatan pendidikan dan latihan bahasa Inggris berbasis pengembangan diri dengan topik ‘daily routines’, 2) memberikan gambaran tentang pengembangan pendekatan praktik pembelajaran bahasa Inggris berbasis pengembangan diri untuk mengembangkan kapasitas peserta diklat. Selama ini, diklat bahasa Inggris lebih menitikberatkan pada penguasaan bahasa dan pengajaran bahasa Inggris. Untuk itu, dikembangkan pendekatan dengan fokus pada pembelajaran bahasa Inggris yang mengarahkan pada optimalisasi pengembangan diri pribadi melalui tugas-tugas yang dilakukan. Pendekatan tulisan terhadap pembelajaran bahasa Inggris berbasis pengembangan diri dilakukan dengan studi pustaka secara komprehensif terhadap sejumlah referensi terkait dengan konsep diklat, konsep pengembangan diri, kebiasaan sehari-hari, dan teori belajar. Tulisan tentang konsep diklat mengingatkan kita bahwa desain dan konten diklat harus disesuaikan dengan perkembangan zaman yang melatih peserta diklat untuk mengembangkan keterampilan berpikir dalam menyelesaikan permasalahan yang dihadapi. Konsep pengembangan diri menunjukkan bahwa melalui praktik kebiasaan sehari-hari yang baik akan membuat kapasitas peserta diklat berkembang. Berdasarkan teori belajar ditunjukkan bahwa pembelajaran akan lebih bermanfaat jika peserta diklat mengetahui keuntungan dari apa yang dipelajari. Disimpulkan bahwa tulisan pengembangan pendekatan pembelajaran bahasa Inggris berbasis pengembangan diri dapat digunakan untuk mengembangkan kapasitas peserta diklat melalui praktik kebiasaan sehari-hari yang berbobot.